Family Values in The Film In Your Dreams (2025): A Discourse-Historical Approach - Ayu Melati Ningsih; Jumino Suhadi; Devy Pratiwi (Edulitics (Education, Literature, and Linguistics) Journal, 2025)
This study examined how ideological tensions between traditional family stability and individual aspiration were discursively constructed in In Your Dreams (2025) through sibling dialogue and dream sequences. Grounded in Ruth Wodak’s Discourse-Historical Approach (DHA) within Critical Discourse Analysis (CDA), the study focused on five core strategies: nomination, predication, argumentation, perspectivization, and intensification/mitigation. Using qualitative textual analysis of selected script excerpts, the research systematically reconstructed argumentative structures through the claim, warrant, conclusion model to identify the operation of the topos of threat and the topos of loss at the micro-linguistic level (lexical choice, modality, metaphor, and pronoun use). The findings demonstrated that family conflict was discursively framed not merely as interpersonal disagreement but as a structured moral negotiation. Nostalgic generalization and mitigation normalized conflict while simultaneously revealing epistemic insecurity, whereas modal intensification and symbolic metaphor in dream sequences amplified perceptions of instability. Through predication, parental figures were constructed as embodying competing moral orientations, sustainability versus passion, without explicit delegitimation, resulting in ideological ambiguity. The dreamscape served as an arena in which these tensions were dramatized and ultimately rearticulated into a hybrid moral resolution. This study contributes to CDA-based film analysis by demonstrating how DHA’s argumentative reconstruction can systematically expose ideological positioning in animated family narratives through explicit micro-linguistic evidence. Future research should integrate multimodal analysis and audience reception to extend the interpretive scope.